Proactivity in legal education for Generations Z and Alpha: a case study - Restrepo Maria Paola Velásquez (TalTech Journal of European Studies)
As the world continues to evolve and transform, the challenge of actively engaging Generations Z and Alpha in the study of law has become apparent. Traditional teaching methods no longer capture the attention or commitment of these digital natives who exhibit apathy towards conventional learning approaches and crave more relevance. Current pedagogical frameworks do not address the unique learning preferences and digital inclinations of younger generations, resulting in low and inadequate engagement, as well as capacity and skills acquisition. This article aims to use proactive tenets to study the learning preferences, challenges and opportunities of Generation Z and Alpha in the context of legal education; identify and propose proactive innovative teaching and learning strategies that integrate digital tools and personalized interactive methods tailored to the needs of these learners and explore the impact of their application in an undergraduate ‘General Commercial Law’ course in terms of student engagement, problem-solving capacities and practical skills development.